Annealing temperature effects on the electrical properties of (K, Na) NbO3 thin film fabricated by a sol-gel process with a citrate precursor solution. (15th March 2016) - Yao, L.; Zhu, K.; Wang, J.; Liu, J.; Qiu, J.; Cheng, M.; Gu, Q.
ABSTRACT: Utilizing the comparatively low cost niobium pentoxide (Nb2 O5 ) as raw material, (K, Na)NbO3 (KNN) thin films were deposited onto Ti substrate by a sol–gel non-alkoxide process. The effects of annealing temperature on the phase, morphology, dielectric, and ferroelectric properties of KNN thin films were investigated. KNN thin films without impurities were obtained above 700°C, and the microstructure of all films were dense and uniform. A maximum dielectric constant of 480 was obtained in the film annealed at 700°C, which is comparable to the film prepared from niobium ethoxide.